The neural basis of gambling disorder: An activation likelihood estimation meta-analysis. (January 2021) - Raimo, Simona; Cropano, Maria; Trojano, Luigi; Santangelo, Gabriella
Highlights: GD was associated with cortical grey-matter thinning in the right PFC. Decision making under risk was associated with hyperactivation in the VS in GD. Loss processing was associated with hypoactivation in the left dorsal ACC in GD. Gain processing was associated with hyperactivation in the PFC and in VS in GD. Abstract: Previous imaging studies suggested that impairments of prefrontal-striatal and limbic circuits are correlated to excessive gambling. However, the neural underpinnings of gambling disorder (GD) continue to be the topic of debate. The present study aimed to identify structural changes in GD and differentiate the specific brain activity patterns associated with decision-making and reward-processing. We performed a systematic review complemented by Activation likelihood estimation (ALE) meta-analyses on morphometric and functional studies on neural correlates of GD. The ALE meta-analysis on structural studies revealed that patients with GD showed significant cortical grey-matter thinning in the right ventrolateral and ventromedial prefrontal cortex compared to healthy subjects. The ALE meta-analyses on functional studies revealed that patients with GD showed a significant hyperactivation in the medial prefrontal cortex and in the right ventral striatum during decision-making and gain processing compared to healthy subjects. These findings suggest that GD is related to an alteration of brain mechanisms underlying top-down control and appraisal of gambling-related stimuli and provided indications to develop new interventions in clinical practice.